Resonant Excitation of Terahertz Surface Plasmons in Subwavelength Metal Holes - Weili Zhang; Abul K. Azad; Jiaguang Han (Active and Passive Electronic Components)
We present a review of experimental studies of resonant excitation of terahertz surface plasmons in two-dimensional arrays of subwavelength metal holes. Resonant transmission efficiency higher than unity was recently achieved when normalized to the area occupied by the holes. The effects of hole shape, hole dimensions, dielectric function of metals, polarization dependence, and array film thickness on resonant terahertz transmission in metal arrays were investigated by the state-of-the-art terahertz time-domain spectroscopy. In particular, extraordinary terahertz transmission was demonstrated in arrays of subwavelength holes made even from Pb, a generally poor metal, and having thickness of only one-third of skin depth. Terahertz surface plasmons have potential applications in terahertz imaging, biosensing, interconnects, and development of integrated plasmonic components for terahertz generation and detection.